Language Politeness Training for Verbal Bullying Prevention: A Pre-Post Intervention Study at Muhammadiyah 3 Plus High School, Bandung (ABDIMAS: Jurnal Pengabdian Masyarakat, 2025)
Verbal bullying remains a serious issue in Indonesian schools, negatively impacting students’ mental health and academic performance. Low awareness and skills in polite communication have been identified as contributing factors. This study aimed to evaluate the effectiveness of a language politeness training program in preventing verbal bullying among high school students. A pre-post intervention design was conducted involving 61 students from Muhammadiyah 3 Plus High School, Bandung City. Data were collected using a validated questionnaire assessing students’ knowledge and awareness of language politeness. A pre-test was administered before the intervention, followed by a structured training session, and a post-test. Data were analyzed using a paired-samples t-test. The average pre-test score was 56.13 (SD = 8.42), and the post-test score increased to 74.03 (SD = 7.95), yielding a mean improvement of 31.90% (t(60) = 12.47, p < 0.001). Students also expressed enthusiasm and provided positive feedback about the training, indicating increased awareness of verbal bullying. The conclusion from this community service is that language politeness training significantly improved students’ communication skills and awareness of verbal bullying. Schools are recommended to integrate such training into ongoing anti-bullying programs. Future studies should incorporate control groups, larger samples, and longitudinal follow-up to strengthen generalizability.